2000
DOI: 10.1038/sj.ejcn.1601065
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D3 and vitamin K1 supplementation of Dutch postmenopausal women with normal and low bone mineral densities: effects on serum 25-hydroxyvitamin D and carboxylated osteocalcin

Abstract: Results: Baseline %carbOC of the entire study population was positively correlated with BMD of the lumbar spine and femoral neck. Correspondingly, women with low BMD had lower %carbOC at baseline than women with normal BMD but this difference disappeared after 1 y of supplementation with vitamin K 1 ((mean + s.d.) 68 + 11% (95% CI, 64.5 ± 71.2%) vs 72 + 6% (95% CI, 70.1 ± 72.9%), respectively). One year of supplementation with vitamin D 3 showed maximum increases in 25(OH)D of 33 + 29% (95% CI, 24.8 ± 41.8%) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 29 publications
0
28
0
1
Order By: Relevance
“…A subsequent study confirmed the beneficial effect of vitamin K1 supplementation on BMD in postmenopausal women, with doses of 80mcg/d phylloquinone proving effective 66 . There were, however, mixed results for MK4, with one trial showing that 45mg/d, together with vitamin D and calcium, had a beneficial effect on BMD in Korean postmenopausal women 71 , while another showed that MK4 enhanced the effect of bisphosphonates in Japanese postmenopausal females 72 but a larger study over three years found no effect on BMD, although BMC and femoral neck width were increased compared to placebo 73 .…”
Section: Bonementioning
confidence: 53%
See 1 more Smart Citation
“…A subsequent study confirmed the beneficial effect of vitamin K1 supplementation on BMD in postmenopausal women, with doses of 80mcg/d phylloquinone proving effective 66 . There were, however, mixed results for MK4, with one trial showing that 45mg/d, together with vitamin D and calcium, had a beneficial effect on BMD in Korean postmenopausal women 71 , while another showed that MK4 enhanced the effect of bisphosphonates in Japanese postmenopausal females 72 but a larger study over three years found no effect on BMD, although BMC and femoral neck width were increased compared to placebo 73 .…”
Section: Bonementioning
confidence: 53%
“…results are mixed with respect to an association between serum ucOC/OC and BMD 63,64,66 , with the ratio being significantly greater in carriers of the apoE4 phenotype, normally a risk factor for atherosclerosis 34 while lower ucOC was associated with apoE2 genotype 49 . This may be due to the apoE4 phenotype giving markedly faster hepatic clearance of chylomicrons and very low density lipoproteins, which lowers circulating vitamin K relative to the apoE2 phenotype 8 .…”
Section: Bonementioning
confidence: 99%
“…One should also question what the prevention of a seasonal decline (a percentage change) has to do with nutritional adequacy (an absolute value). Not only did Schaafsma et al (2000) fail to specify a target in terms of 25(OH)D concentration, they used one lab with one method for healthy subjects, and a different lab with a different method for those with osteoporosis. There was no validation that the two methods used for 25(OH)D assay could produce same result on the same sample.…”
Section: Specify a Suitable Target For Vitamin D Nutritional Adequacymentioning
confidence: 99%
“…Recent issues of this journal have seen two articles highlighting the nutritional need for vitamin D in adults (Schaafsma et al, 2000;Morabia et al, 2000). This editorial is a critical commentary with suggested strategies to make publications relating to vitamin D requirements of practical bene®t to others.…”
Section: Introductionmentioning
confidence: 99%
“…Our paper (Schaafsma et al, 2000) was a sub study on the outcome of a supplement that contained calcium, vitamin D and vitamin K, given to postmenopausal women with normal and low bone mineral density (BMD). The endpoint was BMD after one year, but in the cited paper we only discussed the encountered effects on circulating 25(OH)D and PTH (as vitamin D status indices) and percentage carboxylated osteocalcine (vitamin K index).…”
mentioning
confidence: 99%